Assessing the population structure and genetic diversity of wheat germplasm with the iPBS-retrotransposons marker system - Baran, Nurettin (Csiro Publishing, 2024)
Context Wheat (Triticum aestivum L.) is an important crop that provides food to millions of people all over the world. Currently, wheat production is limited due to various biotic and abiotic stresses resulting from uneven patterns of climate change. Therefore, it is very important to develop climate-resilient wheat cultivars. Crop genetic diversity allows the scientific community to identify genetic variations that can be utilised in the development of improved cultivars. Aims This study planned to characterise the wheat germplasm with the iPBS-retrotransposons marker system. Methods A total of 30 iPBS-retrotransposons markers were screened and among these, the 12 most polymorphic markers were selected for further analysis. Key results Molecular characterisation yielded a total of 170 bands, of which 143 were polymorphic. A substantial level of genetic diversity was observed (mean effective number of alleles: 1.37, Shannon's information index: 0.23, gene diversity: 0.35). Maximum genetic distance was observed in G9 and G60 genotypes. Analysis of molecular variance revealed that most genetic variation (95%) occurred within the populations. The model-based structure algorithm divided the studied germplasm into three populations based on their collection regions. Similarly, the neighbour-joining analysis also divided 70 tested wheat genotypes into three populations, whereas principal coordinate analysis divided the evaluated germplasm into four populations. Conclusions This study confirms the iPBS-retrotransposons as an ideal marker for the genetic diversity assessment studies for any crop, especially for wheat. Implications The results presented here will be helpful for the scientific community in the marker-assisted breeding of wheat.
Keywords: cereals; food security; genetic diversity; germplasm; iPBS-retrotransposons; molecular characterisation; Triticum aestivum; T & uuml;rkiye